SUBCUTANEOUS FILLING OF TEAR DROP IN THE LOWER EYELID: CASE REPORT - Barbosa de Oliveira, Aline; Regina Veronezi, Lauscea; Vivianne Nogueira, Marcia; Rabelo Lima Barbosa, Chrystianne; Rodrigues Ribeiro, Henrique; Lemos Maia, Juliana; Elayne Silva Montezuma, Gina; Januzzi Santos, Marcelo (Health and Society, 2023)
The tear drip, medial portion of the lower part of the orbital cavity, presents a deformity of multifactorial origin, not only affecting patients in the facial aging process. One treatment possibility is to use fillers with specific flexibility characteristics for this region. When applying this technique, we deposit microdots in the subcutaneous tissue throughout the peri-orbicularis oculi region from the medial canthal ligament to the lateral canthal ligament. Approximately 0.4 ml was used on each side (right and left) distributed in application micropoints using the smart click syringe system throughout the lower eyelid in superficial and deeper points of the same subcutaneous layer so as not to concentrate the product under the skin. We chose not to perform overcorrection, since the product used by your Swelling Factor could, over the days, after absorbing water, form pockets in the treated region. The present descriptive observational study aimed to highlight the results of subcutaneous filling with Vital Light Skinboosters in the treatment of tear leakage.